The Medicinal Plant Agrimonia pilosa Ledeb.: Botanical Description, Traditional use, Phytochemistry and Pharmacology - Hop, Nguyen Q.; Son, Ninh The (Combinatorial Chemistry & High Throughput Screening, 2023)
Background: Hairy agrimony (Agrimonia pilosa Ledeb.) is a traditional medicinal plant widely used in Eastern Europe and Eastern Asia. The plant is harvested as it comes into flower and could be dried for later usage. Hairy agrimony has been traditionally introduced to treat sore throat, abdominal pain, headache, mucoid dysentery, bloody and white discharge, parasites, and eczema. Objective: Since the 1950s, various experimental reports relating to phytochemical and pharmacological aspects have been observed, but an overview is now not available. The current paper emphasizes on in-depth information about the botanical description, traditional use, phytochemistry, and pharmacology. Methods: The collection of previous research is basically dependent on the reliable resources Sci- Finder, Google Scholar, ScienceDirect, reputation publishers, and thesis books. Results: A. pilosa was found to contain a variety of chemical classes. To date, more than 160 secondary metabolites have been separated, and the derivatives type flavonoids, phloroglucinols, tannins, isocoumarins, and triterpenoids are the main components. A. pilosa crude extracts and their isolates set a broad panel of pharmacological values, including anti-cancer, anti-microbial, antivirus, anti-oxidant, anti-inflammation, anti-diabetes, anti-osteosarcoma, anti-aging, anti-nociception, anti-adipogenesis, anti-leishmaniasis, estrogenic-like activity, neuroprotective and hepatoprotective activities, and vascular relaxation. Conclusion: In vitro and in vivo results also successfully explained the pharmacological mechanisms of A. pilosa constituents. More bioassay-guided phytochemical and clinical studies are necessary.
Keywords: phytochemistry